Prevalencia de Demódex canis que presenten lesiones cutáneas en el cantón Naranjito - Gavilánez Quinto, Carmen Elizabeth (2023)
Demodex canis is a type of mite that resides in the skin of animals, specifically in the hair follicles and ocasionally in the sebaceous glands of canines. The presence of inflammatory lesions in the animal's skin is an indicator of the existence of this mite, it is present in a specific area or in the whole animal's physique. It is considered relevant to mention that D. canis can affect all canines, but there are certain breeds that are more prone to suffer from it, such as the American pitbull terrier, Doberman, and others. The reason behind this work is to check the number of canines affected by D. canis in the cantón Naranjito, 100 canines were sampled (males and females), this was checked by the deep scraping technique, from this came out (52 positive cases for D. canis), (7 positive cases for Allergic Dermatitis), (15 positive cases for Flea Allergic Dermatitis), (5 positive cases for Atopic Dermatitis), (1 positive case for Dermatitis of the cutaneous folds), (1 positive case for Dermatitis due to Malassezia pachydermatis), (18 positive cases for Sarcoptes scabiei), (1 positive case for otodectic mange), this study was not related to age, sex, breed, since the canines presenting this disease were of all ages